Conceptual Model of Fintech Information System Services Adoption for Impact and Transformation Workers in Vocational Context - Ade Andri Hendriadi; Isma Widiaty; Iwan Kustiawan (Green Publisher Indonesia, 2025)
This study develops and tests a conceptual model of fintech information systems services adoption for impact and transformation workers in vocational context in Indonesia. Through a mixed-method approach with 618 respondents, the study identified complex interactions between individual characteristics, organizational factors, and barriers to adoption, as well as their effects on system quality and adoption impacts. The results showed that individual characteristics were the strongest determinants (β = 0.684) of fintech adoption, followed by organizational factors (β = 0.572) and barriers to adoption (β = -0.428). System quality (β = 0.745) acts as the main mediator, influencing the level of use that impacts four dimensions: individual (β = 0.682), organizational (β = 0.624), process (β = 0.594), and technological (β = 0.568). This model offers a comprehensive framework for understanding and managing fintech adoption in a vocational environment, with significant implications for practitioners, organizations, and policymakers.